PS8:161 The disease burden in patients with longstanding systemic lupus erythematosus: focus on health resource use and costs. (21st March 2018) - Tani, C; Lorenzoni, V; Vagelli, R; Stagnaro, C; Elefante, E; Carli, L; Turchetti, G; Mosca, M
Abstract : Introduction: As a consequence of increased SLE patients survival, patients with long disease duration represent a significant proportion of our cohorts. This study aims to evaluate health resource use and the 6 months costs in patients with SLE with long disease duration. Methods: The economic evaluation was performed in terms of cost-of-illness analysis as part of a larger study enrolling SLE patients with at least 15 years of disease duration regularly followed at our unit. At enrollment, the following information were collected: disease activity (SLEDAI), organ damage (SLICC-DI score), comorbidities, treatment patterns; in addition to clinical data, patients were required to complete an ad-hoc questionnaire for the collection of facts relevant for the estimation of the economic dimension and covering the previous six-months. Such a time frame was considered to be appropriate as recall period. Direct health (drugs, hospitalizations, emergency visits, specialists visits, laboratory tests and instrumental examination) and non-health costs (transportation and accommodation) as well as indirect costs because of productivity loss were estimated. Results: 51 adult patients with long disease duration were recruited (98% female, mean age 49±11 years, median disease duration 17 years, IQR 15–23). Median (IQR) SLEDAI score was 2 (0–4), median SLICC-DI was 1 (0–2). The median (IQR) direct health costs per patients over the previous 6 months resulted 410€ (201–1687); indirect costs because of productivity lost were 130€ (0–356). The median overall cost to the Society was 473€ (327–2148); the presence of comorbid conditions resulted associated with higher overall cost for the Society (552€ [327–1807] vs 264€ [94–1164] p=0.046); disease activity and damage at enrollment were not associated with costs increase in this cohort. Conclusions: This cohort of patients with long lasting disease is characterised by low disease activity and mild organ damage; in this setting, the disease burden on the single patient and family is significant and the costs to the Society are influenced by the presence of comorbidities.